Pengaruh Teknologi dan Literasi Keuangan Terhadap Kinerja UMKM di Kota Batam - Siti Nur Artika; Neni Marlina Br Purba (SCIENTIA JOURNAL, 2025)
MSMEs play a crucial role in regional economic growth, including in Batam City. Despite their potential, many MSMEs still face challenges such as low revenue, imbalance between capital and assets, and limited use of digital technology and financial knowledge. Many MSME owners lack financial recording practices and manage their businesses conventionally without leveraging digital platforms such as e-commerce, social media, and digital payment systems. This study aims to examine the influence of technology and financial literacy on MSME performance, both partially and simultaneously. A quantitative approach was used, employing multiple linear regression analysis. The sample consisted of 110 culinary MSMEs in Batam City that had operated for at least two years and used digital tools. Data were collected via an online questionnaire and analyzed using SPSS version 29. The results indicate that both technology and financial literacy positively and significantly affect MSME performance, both individually and together. These findings highlight the importance of strengthening financial skills and optimizing digital tools to improve MSME performance. The study suggests that digital and financial literacy should be key focus areas for MSME development programs, both by the government and support institutions.